2020
DOI: 10.3390/ijerph17103693
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cybervictimization on Psychological Adjustment in Adolescence: Analyzing the Role of Emotional Intelligence

Abstract: Cybervictimization has been associated with serious emotional adjustment problems such as low self-concept and depressive symptomatology. In addition, these problems can negatively affect the well-being of the victims, manifesting in their levels of satisfaction with life. However, it should be noted that not all cybervictims develop these consequences with the same intensity. These differences seem to be related to the development of emotional intelligence (EI), as it can positively influence adolescents’ emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
5
14
1
5
Order By: Relevance
“…Furthermore, EI was negatively related to suicidal ideation in both studies. These findings are consistent with previous research suggesting that EI abilities seem to serve as protective factors against mental health problems and suicidal ideation [ 3 , 9 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, EI was negatively related to suicidal ideation in both studies. These findings are consistent with previous research suggesting that EI abilities seem to serve as protective factors against mental health problems and suicidal ideation [ 3 , 9 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…During adolescence, EI has proved to be a protective factor for both suicidal ideation and suicide attempts in samples of adolescents without a history of traumatic events [ 8 , 14 ]. More interestingly, EI also has been found to mitigate the negative influence of cyberbullying and bullying on emotional adjustment (e.g., depressive symptomatology) [ 9 , 15 ] and suicidal ideation/behaviours [ 16 ]. Similarly, previous research confirmed that, among depressed adolescents, high EI protects against suicidal ideation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Socio-emotional skills are necessary among students, both inside and outside the classroom [32,33]. Multidimensional analyses of EI in cases of cybervictimization have discovered that cybervictims pay considerable attention to their own emotions (emotional attention) but have difficulties understanding and managing them [34][35][36].…”
Section: Emotional Intelligence (Ei) Education and Academic Performmentioning
confidence: 99%
“…To do this, we consider it necessary to develop identity in a tight way in the adolescent stage to avoid this occurring at later educational stages, such as at university, and to continue to address problems in interpersonal relationships and abuse of the internet [ 26 ]. Similarly, it is necessary to promote self-esteem [ 23 ], coping strategies [ 52 ], emotional regulation [ 2 , 4 , 6 , 7 , 8 , 9 , 53 ], skills for conflict resolution and stress management, self-control, social and communication skills, and healthy leisure activities [ 16 , 19 , 20 , 54 ]. The family also has a relevant role to play in preventing internet addiction [ 6 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%